Закономірності поведінки точності оптичних призм зовнішнього відбиття - Маслов, В.П. (Вісник Українського матеріалознавчого товариства, 2013)
Shown that the adhesive bonding with micro- and nanofillers provide long-term strength and stability accuracy parameters mirrored prisms and can compete with the precision of diffusion nanobonding. For example mirrored prisms external reflection revealed a general pattern of behavior error after the technological and extreme factors corresponding inverse exponential dependence on time. It is supposed, that this reduction is associated with reverse mikrocreep under accumulated tension.